Childhood bullying and mental health: understanding risk, resilience, and the role of anti-bullying interventions - Guzman Holst, C (2023)
The primary focus of this thesis is to explore the relationship between bullying and mental health in children and young people. Globally 8-45% of children and young people are victims of bullying (Biswas et al., 2020). While most children and young people experience low and stable trajectories of bulling victimisation and/or perpetration throughout the school years, a few experience chronic and increasing levels of victimisation and/or perpetration (Barker et al., 2008). Children and young people in these latter groups are more likely to have elevated levels of mental health problems (Singham et al., 2017). It is widely known that there is a strong reciprocal association between bullying victimisation and mental health problems, however practical and methodological limitations in studying bullying (victimisation and perpetration) make it difficult to draw causal assumptions and establish what mechanisms and factors influence this relationship (Guzman-Holst & Bowes, 2021). The best approaches to study causal effects are natural experiments, longitudinal data, and randomised controlled trials of interventions. This thesis combines all these approaches to examine the relationship between bullying and mental health across different contexts.